Inter-sectoral dynamics of the global fisheries carbon footprint: a multi-regional input-output analysis within the principle of common but differentiated responsibilities - Wang, Chong; Liu, Xufeng; Li, Ke; Wei, Chunzhu; Xie, Mingcong (Frontiers in Marine Science, 2025)
Fisheries are a critical source of animal protein for billions globally, yet the intensification of aquaculture has increased reliance on artificial inputs, raising concerns over associated carbon emissions. This study analyzes the spatial distribution and temporal trends of global seafood production, consumption, and related carbon emissions from 2015 to 2020, using the Eora26 and Food and Agriculture Biomass Input-Output (FABIO) multi-regional input-output databases. Special attention is given to the carbon footprint of fishmeal and fish oil across economic sectors. Findings reveal that Asia, particularly China, dominates global seafood production, accounting for 39.2% of output and contributing significantly to spatial disparities in fisheries-related emissions. From 2015 to 2020, global seafood-related carbon emissions rose by 31.6%, with East Asia consistently ranking highest across domestic, consumption-based, and production-based emissions. South America increasingly serves as a major exporter, meeting rising global seafood demand. Fishmeal and fish oil are primarily consumed in the fisheries, cattle, pig, and dairy sectors. China is the largest recipient, while Norway, Peru, Chile, and the United States are key producers. The carbon footprint of these intermediate products exhibits scaling law characteristics, reflecting the complexity and transboundary nature of their supply chains. This study highlights the spatial and industrial intricacies of seafood-related carbon emissions and underscores the need for more targeted, sector-specific mitigation strategies. The findings also emphasize the importance of applying the principle of common but differentiated responsibilities to ensure equitable carbon reduction across regions within the global fisheries system.